Using Case Based Reasoning to Answer Exam Questions - Tanawong, Tawin (Naresuan University Journal: Science and Technology (NUJST); Vol 21 No 3 (2013): September-December 2013, 2014)
There are various uses to the knowledge source for the Tutorial System that is interesting and important to the expert system fields in an Artificial Intelligent development in the previous research studies.  However we are interested in the questioning answering system which is applied to use the answering question test system in the formats of the previous exam question solving to the new exam question solving so that it can be given from the background knowledge in various ways such as the heuristics, experiences, textbooks and expertise, etc.  The main point of our research is how we could give the knowledge from all of the sources to help for solving a new problem.      This paper shows how to use the case based reasoning to answer the questions. There are two parts in this paper.  The first one is describing the relationship between the old case and new problem which have similar cases and the second one is applying the previous cases solving for new exam answering for the new solution.  The main approaches for case retrieved with the process are the retrieve matching cases to the exam questions.  The exam question forms are the key structural classification by the ontology and the other one is in the forms of the different knowledge structures but both are in the same question forms.  We use the previous solving procedures to adapt the new solution problem solving and present respectively two cases, a problem description and solving procedure. Keywords: Case-based reasoning, Ontology, Knowledge representation, Questioning-Answering system
Keywords: Case-based reasoning, Ontology, Knowledge representation, Questioning-Answering system